Anticorrosive Teflon coating as well as preparation method and application thereof
By using radiation-modified polytetrafluoroethylene powder and graphene oxide in anticorrosion coatings, a composite of modified graphene and Teflon primer is formed, and the porous coating caused by excessive zinc powder content is solved. and the problem of degradation of adhesion, achieving excellent performance in high wear resistance and high corrosion environments.
Patent Information
- Application Number
- CN202411822145.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Excessive zinc powder content in existing anticorrosion coatings leads to porous and reduced adhesion of the coating, affecting corrosion resistance, and especially in high wear and high corrosion environments.
Using a preparation method of anticorrosive Teflon coating, the modified graphene and Teflon are formed by combining modified polytetrafluoroethylene powder with graphene oxide, dopamine hydrochloride and phosphorus trichloride under irradiation conditions. The composite of primer improves the mechanical properties and corrosion resistance of the coating.
It significantly improves the high temperature resistance, rust resistance, mechanical properties, wear resistance and scratch resistance of the paint, can effectively resist high wear resistance and high corrosion environments, and enhances the comprehensive performance of the coating.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to an anti-corrosion Teflon coating and a preparation method and application thereof. Background Art
[0002] Teflon coating is an industrial coating with polytetrafluoroethylene (PTFE) as the main component. It has many excellent properties, such as non-stickiness, heat resistance, sliding, moisture resistance, wear resistance, and corrosion resistance, which makes it widely used in many industries.
[0003] In recent years, the research on anti-corrosion coatings has been very rapid. On the basis of traditional conventional anti-corrosion coatings, many varieties with excellent performance have been developed. Among them, the commonly used anti-corrosion coating is epoxy zinc-rich coating. Epoxy zinc-rich coating is a heavy-duty anti-corrosion coating with excellent corrosion resistance and is widely used in the field of heavy metal corrosion protection. Zinc in epoxy zinc-rich coating is a sacrificial anode, and its content in the coating is usually greater than 70%. However, due to the high content of zinc powder in the coating, the coating is prone to being porous and the adhesion is reduced. In addition, the zinc-rich coating produces more zinc salts when it plays a cathodic protection role, which affects the bonding force between the upper coating and the zinc-rich coating, thereby reducing the anti-corrosion performance of the coating. Summary of the invention
[0004] The purpose of the present invention is to propose an anti-corrosion Teflon coating and its preparation method and application, which has good high temperature resistance, corrosion resistance, rust resistance, mechanical properties, wear resistance, scratch resistance, medium resistance and other properties, can effectively resist high wear-resistant environments such as sliding friction, impact friction, cavitation friction, as well as high corrosion environments such as acidic media and alkaline media, and has broad application prospects.
[0005] The technical solution of the present invention is achieved in this way:
[0006] 1. The present invention provides a method for preparing an anti-corrosion Teflon coating, characterized in that it comprises the following steps:
[0007] S1. Add polytetrafluoroethylene powder to Augeo SL-191 solvent, add glycidyl methacrylate, polymerization inhibitor and sensitizer under irradiation conditions, introduce inert gas, heat and stir to react, extract with acetone after the reaction, and dry to obtain modified Teflon powder; the mass ratio of polytetrafluoroethylene powder, glycidyl methacrylate, polymerization inhibitor and sensitizer is 10:2-3:0.01-0.02:0.02-0.05;
[0008] S2. adding graphene oxide to water, adding dopamine hydrochloride and a catalyst, heating and stirring the reaction, filtering, washing, and drying to obtain modified graphene oxide; the mass ratio of the graphene oxide, dopamine hydrochloride and the catalyst is 10:3-4:0.5-1;
[0009] S3. reducing the modified graphene oxide by hydrazine hydrate vapor to obtain modified graphene;
[0010] S4. The phosphorus oxychloride and the modified graphene are added to a solvent, heated and stirred to react, centrifuged, washed, and dried to obtain a composite; the mass ratio of the phosphorus oxychloride to the modified graphene is 3-4:10;
[0011] S5. The modified Teflon powder and the composite are added to the Teflon primer, stirred to react, and an anti-corrosion Teflon coating is obtained; the mass ratio of the modified Teflon powder, the composite, and the Teflon primer is 10:3-5:75-85.
[0012] As a further improvement of the present invention, the temperature of the irradiation conditions in step S1 is 100-150°C, the total irradiation dose is 12-15 kGy, the inhibitor is ammonium ferrous sulfate, the sensitizer is concentrated sulfuric acid, the temperature of the heating and stirring reaction is 60-70°C, and the time of the heating and stirring reaction is 3-5h.
[0013] As a further improvement of the present invention, the catalyst in step S2 is a Tris-HCl solution with a pH of 9-10, the temperature of the heating and stirring reaction is 45-55° C., and the time of the heating and stirring reaction is 1-3 h.
[0014] As a further improvement of the present invention, the reduction time in step S3 is 7-10 hours.
[0015] As a further improvement of the present invention, the solvent in step S4 is selected from at least one of ethyl acetate, dichloromethane, acetone, tetrahydrofuran, and N,N-dimethylformamide, the temperature of the heating and stirring reaction is 75-85° C., and the time of the heating and stirring reaction is 2-4 hours.
[0016] As a further improvement of the present invention, the stirring reaction time in step S5 is 7-10 hours.
[0017] As a further improvement of the present invention, the present invention specifically comprises the following steps:
[0018] S1. Add 10 parts by weight of polytetrafluoroethylene powder to Augeo SL-191 solvent, irradiate at a temperature of 100-150°C, irradiate at a total dose of 12-15 kGy, add 2-3 parts by weight of glycidyl methacrylate, 0.01-0.02 parts by weight of ammonium ferrous sulfate and 0.02-0.05 g of concentrated sulfuric acid, introduce nitrogen, heat to 60-70°C, stir to react for 3-5 hours, extract with acetone for 24 hours after the reaction is completed, and dry to obtain modified Teflon powder;
[0019] S2. adding 10 parts by weight of graphene oxide to water, adding 3-4 parts by weight of dopamine hydrochloride and 0.5-1 parts by weight of a catalyst, heating to 45-55° C., stirring for 1-3 hours, filtering, washing, and drying to obtain modified graphene oxide;
[0020] The catalyst is a Tris-HCl solution with a pH of 9-10;
[0021] S3. The modified graphene oxide is reduced by hydrazine hydrate vapor for 7-10h to obtain modified graphene;
[0022] S4. 3-4 parts by weight of phosphorus oxychloride and 10 parts by weight of modified graphene are added to a solvent, heated to 75-85° C., stirred for reaction for 2-4 hours, centrifuged, washed, and dried to obtain a composite;
[0023] S5. Add 10 parts by weight of modified Teflon powder and 3-5 parts by weight of the composite into 75-85 parts by weight of Teflon primer, and stir to react for 7-10 hours to obtain an anti-corrosion Teflon coating.
[0024] The present invention further protects an anti-corrosion Teflon coating, which is prepared by the above-mentioned preparation method.
[0025] The present invention further protects the use of the above-mentioned anticorrosive Teflon coating in preparing kitchenware coating.
[0026] The present invention has the following beneficial effects:
[0027] The invention uses electron beam or gamma ray irradiation to break CC bonds and CF on the Teflon polytetrafluoroethylene chain to generate free radicals, and utilizes the free radicals to initiate a grafting reaction of glycidyl methacrylate monomer on the surface of the Teflon polytetrafluoroethylene, thereby improving the polarity of PTFE and further increasing its compatibility and reactivity with other substances. The grafted modified Teflon powder can undergo a ring-opening reaction with the modified graphite powder with amino groups on the surface, so that the modified graphite powder can be evenly dispersed in the Teflon coating, thereby improving the compatibility of the inorganic particles, thereby greatly improving the mechanical properties, wear resistance, rust resistance, medium resistance and other characteristics of the coating.
[0028] The Augeo SL-191 used in the present invention is a new type of hydrophilic and lipophilic, environmentally friendly solvent developed by Rhodia Company. It has a high boiling point, is colorless and odorless, has a low volatilization rate, and is non-toxic to human health and the environment.
[0029] The present invention modifies the surface of graphene oxide by polydopamine so that the surface of the graphene oxide has rich amino groups. Meanwhile, the modified graphene is reduced by hydrazine hydrate vapor to obtain the modified graphene. After the modified graphene is added to Teflon primer, the pores of the coating become smaller, the anti-corrosion performance is enhanced, and the mechanical properties and wear resistance are significantly improved. The introduction of the modified graphene into the coating improves the comprehensive performance of the coating.
[0030] The present invention then utilizes the modified graphene to react with phosphorus oxychloride to obtain a composite material, wherein the chlorine atom undergoes a nucleophilic substitution reaction at the amino group, so that the phosphorus oxychloride is grafted on the surface of the modified graphene. On the one hand, the high temperature resistance of the coating is improved, and at the same time, the phosphorus element can also form a complex with the metal ion to obtain a solid protective layer. This dense passivation layer is insoluble in water, has high hardness, and has good anti-corrosion and anti-rust effects.
[0031] The anti-corrosion Teflon coating prepared by the present invention has good high temperature resistance, corrosion resistance, rust resistance, mechanical properties, wear resistance, scratch resistance, medium resistance and other properties, can effectively resist high wear resistance environments such as sliding friction, impact friction, cavitation friction, as well as high corrosion environments such as acidic media and alkaline media, and has broad application prospects. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Graphene oxide, purity > 99%, thickness < 5 nm, oxygen content of about 35%, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; polytetrafluoroethylene powder, water content < 0.05%, purchased from Shenyang Wuliang Technology Co., Ltd.; Teflon primer, purchased from Chemours 420G-703; Augeo SL-191, purchased from Rhodia.
[0034] Example 1
[0035] This embodiment provides a method for preparing an anti-corrosion Teflon coating, comprising the following steps:
[0036] S1. Add 10g polytetrafluoroethylene powder into 200mL Augeo SL-191 solvent, irradiate at 100℃, irradiate with a total dose of 12kGy, add 2g glycidyl methacrylate, 0.01g ammonium ferrous sulfate and 0.02g concentrated sulfuric acid, introduce nitrogen, heat to 60℃, stir to react for 3h, extract with acetone for 24h after the reaction, and dry to obtain modified Teflon powder;
[0037] S2. Add 10 g of graphene oxide to 200 mL of water, add 3 g of dopamine hydrochloride and 0.5 g of catalyst, heat to 45° C., stir to react for 1 h, filter, wash, and dry to obtain modified graphene oxide;
[0038] The catalyst is a Tris-HCl solution with a pH of 9;
[0039] S3. The modified graphene oxide was reduced by hydrazine hydrate vapor for 7 hours to obtain modified graphene;
[0040] S4. 3 g of phosphorus oxychloride and 10 g of modified graphene were added to 200 mL of solvent, heated to 75 ° C, stirred for reaction for 2 h, centrifuged, washed, and dried to obtain a composite;
[0041] S5. Add 10 g of modified Teflon powder and 3 g of the composite into 75 g of Teflon primer, stir and react for 7 h to obtain an anti-corrosion Teflon coating.
[0042] Example 2
[0043] This embodiment provides a method for preparing an anti-corrosion Teflon coating, comprising the following steps:
[0044] S1. Add 10g polytetrafluoroethylene powder into 200mL Augeo SL-191 solvent, irradiate at 150℃, irradiate with a total dose of 15kGy, add 3g glycidyl methacrylate, 0.02g ammonium ferrous sulfate and 0.05g concentrated sulfuric acid, introduce nitrogen, heat to 70℃, stir and react for 5h, extract with acetone for 24h after the reaction, and dry to obtain modified Teflon powder;
[0045] S2. Add 10 g of graphene oxide to 200 mL of water, add 4 g of dopamine hydrochloride and 1 g of catalyst, heat to 55° C., stir and react for 3 h, filter, wash and dry to obtain modified graphene oxide;
[0046] The catalyst is a Tris-HCl solution with a pH of 10;
[0047] S3. The modified graphene oxide was reduced by hydrazine hydrate vapor for 10 h to obtain modified graphene;
[0048] S4. 4 g of phosphorus oxychloride and 10 g of modified graphene were added to 200 mL of solvent, heated to 85 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain a composite;
[0049] S5. Add 10 g of modified Teflon powder and 5 g of the composite into 85 g of Teflon primer, stir and react for 10 h to obtain an anti-corrosion Teflon coating.
[0050] Example 3
[0051] This embodiment provides a method for preparing an anti-corrosion Teflon coating, comprising the following steps:
[0052] S1. Add 10g polytetrafluoroethylene powder into 200mL Augeo SL-191 solvent, irradiate at 125°C, irradiate with a total dose of 13kGy, add 2.5g glycidyl methacrylate, 0.015g ammonium ferrous sulfate and 0.03g concentrated sulfuric acid, introduce nitrogen, heat to 65°C, stir to react for 4h, extract with acetone for 24h after the reaction, and dry to obtain modified Teflon powder;
[0053] S2. Add 10 g of graphene oxide to 200 mL of water, add 3.5 g of dopamine hydrochloride and 0.7 g of catalyst, heat to 50° C., stir and react for 2 h, filter, wash and dry to obtain modified graphene oxide;
[0054] The catalyst is a Tris-HCl solution with a pH of 9.5;
[0055] S3. The modified graphene oxide was reduced by hydrazine hydrate vapor for 8 h to obtain modified graphene;
[0056] S4. 3.5 g of phosphorus oxychloride and 10 g of modified graphene were added to 200 mL of solvent, heated to 80° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain a composite;
[0057] S5. Add 10 g of modified Teflon powder and 4 g of the composite into 80 g of Teflon primer, stir and react for 8 h to obtain an anti-corrosion Teflon coating.
[0058] Comparative Example 1
[0059] Compared with Example 3, the difference is that step S2 is not performed.
[0060] The details are as follows:
[0061] S1. Add 10g polytetrafluoroethylene powder into 200mL Augeo SL-191 solvent, irradiate at 125°C, irradiate with a total dose of 13kGy, add 2.5g glycidyl methacrylate, 0.015g ammonium ferrous sulfate and 0.03g concentrated sulfuric acid, introduce nitrogen, heat to 65°C, stir to react for 4h, extract with acetone for 24h after the reaction, and dry to obtain modified Teflon powder;
[0062] S2. The graphene oxide was reduced by hydrazine hydrate vapor for 8 hours to obtain graphene;
[0063] S3. 3.5 g of phosphorus oxychloride and 10 g of graphene were added to 200 mL of solvent, heated to 80° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain a composite;
[0064] S4. Add 10 g of modified Teflon powder and 4 g of the composite into 80 g of Teflon primer, stir and react for 8 h to obtain an anti-corrosion Teflon coating.
[0065] Comparative Example 2
[0066] Compared with Example 3, the difference is that step S3 is not performed.
[0067] The details are as follows:
[0068] S1. Add 10g polytetrafluoroethylene powder into 200mL Augeo SL-191 solvent, irradiate at 125°C, irradiate with a total dose of 13kGy, add 2.5g glycidyl methacrylate, 0.015g ammonium ferrous sulfate and 0.03g concentrated sulfuric acid, introduce nitrogen, heat to 65°C, stir to react for 4h, extract with acetone for 24h after the reaction, and dry to obtain modified Teflon powder;
[0069] S2. Add 10 g of graphene oxide to 200 mL of water, add 3.5 g of dopamine hydrochloride and 0.7 g of catalyst, heat to 50° C., stir and react for 2 h, filter, wash and dry to obtain modified graphene oxide;
[0070] The catalyst is a Tris-HCl solution with a pH of 9.5;
[0071] S3. 3.5 g of phosphorus oxychloride and 10 g of modified graphene oxide were added to 200 mL of solvent, heated to 80° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain a composite;
[0072] S4. Add 10 g of modified Teflon powder and 4 g of the composite into 80 g of Teflon primer, stir and react for 8 h to obtain an anti-corrosion Teflon coating.
[0073] Comparative Example 3
[0074] Compared with Example 3, the difference is that step S4 is not performed.
[0075] The details are as follows:
[0076] S1. Add 10g polytetrafluoroethylene powder into 200mL Augeo SL-191 solvent, irradiate at 125°C, irradiate with a total dose of 13kGy, add 2.5g glycidyl methacrylate, 0.015g ammonium ferrous sulfate and 0.03g concentrated sulfuric acid, introduce nitrogen, heat to 65°C, stir to react for 4h, extract with acetone for 24h after the reaction, and dry to obtain modified Teflon powder;
[0077] S2. Add 10 g of graphene oxide to 200 mL of water, add 3.5 g of dopamine hydrochloride and 0.7 g of catalyst, heat to 50° C., stir and react for 2 h, filter, wash and dry to obtain modified graphene oxide;
[0078] The catalyst is a Tris-HCl solution with a pH of 9.5;
[0079] S3. The modified graphene oxide was reduced by hydrazine hydrate vapor for 8 h to obtain modified graphene;
[0080] S4. 10 g of modified Teflon powder and 4 g of modified graphene were added to 80 g of Teflon primer, and the mixture was stirred and reacted for 8 h to obtain an anti-corrosion Teflon coating.
[0081] Comparative Example 4
[0082] Compared with Example 3, the difference is that in step S5, the modified Teflon powder is replaced by an equal amount of polytetrafluoroethylene powder.
[0083] The details are as follows:
[0084] S1. Add 10 g of graphene oxide to 200 mL of water, add 3.5 g of dopamine hydrochloride and 0.7 g of catalyst, heat to 50°C, stir and react for 2 h, filter, wash and dry to obtain modified graphene oxide;
[0085] The catalyst is a Tris-HCl solution with a pH of 9.5;
[0086] S2. The modified graphene oxide was reduced by hydrazine hydrate vapor for 8 h to obtain modified graphene;
[0087] S3. 3.5 g of phosphorus oxychloride and 10 g of modified graphene were added to 200 mL of solvent, heated to 80° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain a composite;
[0088] S4. Add 10 g of polytetrafluoroethylene powder and 4 g of the composite into 80 g of Teflon primer, stir and react for 8 h to obtain an anti-corrosion Teflon coating.
[0089] Test Example 1
[0090] The anticorrosive Teflon coatings prepared in Examples 1-3 and Comparative Examples 1-4 were sprayed onto the surface of the stainless steel with primer, with a thickness of about 20 μm. The pencil hardness of the coating was measured according to GB / T 6739-2006. The scratch resistance of the coating was measured using a scratch resistance tester according to ASTM D2197-2016. The adhesion of the paint film was tested according to GB / T 9286-1998, and the test piece was divided into 5×5 small grids with a blade, and adhered with transparent tape, and the tape was removed to observe the integrity of the paint film. The results are shown in Table 1.
[0091] Table 1
[0092] Group Hardness (H) Scratch resistance (kg) Adhesion (grade) Example 1 3 10 0 Example 2 3 11 0 Example 3 3 12 0 Comparative Example 1 1 5 2 Comparative Example 2 2 6 1 Comparative Example 3 2 8 1 Comparative Example 4 1 5 3
[0093] It can be seen from the above table that the anti-corrosion Teflon coatings prepared in Examples 1-3 of the present invention have good comprehensive properties.
[0094] Test Example 2
[0095] The anticorrosive Teflon coatings prepared in Examples 1-3 and Comparative Examples 1-4 were sprayed onto the surface of stainless steel with primer, with a thickness of about 20 μm. The test was carried out in accordance with the provisions of Method A of GB / T 9274-1988. After soaking at room temperature for 14 days, the coating was taken out and cleaned, and the coating was immediately checked for softening, blistering, etc. The acid and alkali resistance of the coating was determined in accordance with GB1763-1979. The test pieces were placed in an acid and alkali test box in turn, and dilute hydrochloric acid was added to the left side and NaOH solution was added to the right side. The coating film was observed every 1 hour to see if it was cracked or damaged, and the time from adding the solution to the damage of the coating film was recorded. The results are shown in Table 2.
[0096] Table 2
[0097] Group Kerosene resistance (RP-3 kerosene, 23±2℃, 14d) Gasoline resistance (180# gasoline, 23±2℃, 14d) Hydraulic oil resistance (15# hydraulic oil, 23±2℃, 14d) Acid resistance (h) Alkali resistance (h) Example 1 No softening, no blistering, no wrinkling, no cracking No softening, no blistering, no wrinkling, no cracking No softening, no blistering, no wrinkling, no cracking 157 172 Example 2 No softening, no blistering, no wrinkling, no cracking No softening, no blistering, no wrinkling, no cracking No softening, no blistering, no wrinkling, no cracking 159 174 Example 3 No softening, no blistering, no wrinkling, no cracking No softening, no blistering, no wrinkling, no cracking No softening, no blistering, no wrinkling, no cracking 162 175 Comparative Example 1 Softening, blistering, wrinkling, cracking Softening, blistering, wrinkling, cracking Softening, blistering, wrinkling, cracking 117 132 Comparative Example 2 Slightly soft, slightly bubbling, slightly wrinkled and cracked Slightly soft, slightly bubbling, slightly wrinkled and cracked Slightly soft, slightly bubbling, slightly wrinkled and cracked 135 147 Comparative Example 3 Slightly soft, slightly bubbling, slightly wrinkled and cracked Slightly soft, slightly bubbling, slightly wrinkled and cracked Slightly soft, slightly bubbling, slightly wrinkled and cracked 128 139 Comparative Example 4 Softening, blistering, wrinkling, cracking Softening, blistering, wrinkling, cracking Softening, blistering, wrinkling, cracking 78 85
[0098] It can be seen from the above table that the anti-corrosion Teflon coatings prepared in Examples 1-3 of the present invention have good corrosion resistance.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an anti-corrosion Teflon coating, characterized in that: The following steps are involved: S1. Add polytetrafluoroethylene powder to Augeo SL-191 solvent, add glycidyl methacrylate, polymerization inhibitor and sensitizer under irradiation conditions, introduce inert gas, heat and stir to react, extract with acetone after the reaction, and dry to obtain modified Teflon powder; the mass ratio of polytetrafluoroethylene powder, glycidyl methacrylate, polymerization inhibitor and sensitizer is 10:2-3:0.01-0.02:0.02-0.05; S2. adding graphene oxide to water, adding dopamine hydrochloride and a catalyst, heating and stirring the reaction, filtering, washing, and drying to obtain modified graphene oxide; the mass ratio of the graphene oxide, dopamine hydrochloride and the catalyst is 10:3-4:0.5-1; S3. reducing the modified graphene oxide by hydrazine hydrate vapor to obtain modified graphene; S4. The phosphorus oxychloride and the modified graphene are added to a solvent, heated and stirred to react, centrifuged, washed, and dried to obtain a composite; the mass ratio of the phosphorus oxychloride to the modified graphene is 3-4:10; S5. The modified Teflon powder and the composite are added to the Teflon primer, stirred to react, and an anti-corrosion Teflon coating is obtained; the mass ratio of the modified Teflon powder, the composite, and the Teflon primer is 10:3-5:75-85.
2. The preparation method according to claim 1, characterized in that: The temperature of the irradiation condition in step S1 is 100-150°C, the total irradiation dose is 12-15 kGy, the inhibitor is ammonium ferrous sulfate, the sensitizer is concentrated sulfuric acid, the temperature of the heating and stirring reaction is 60-70°C, and the time of the heating and stirring reaction is 3-5h.
3. The preparation method according to claim 1, characterized in that: In step S2, the catalyst is a Tris-HCl solution with a pH of 9-10, the temperature of the heating and stirring reaction is 45-55° C., and the time of the heating and stirring reaction is 1-3 hours.
4. The preparation method according to claim 1, characterized in that: The reduction time in step S3 is 7-10 hours.
5. The preparation method according to claim 1, characterized in that: In step S4, the solvent is selected from at least one of ethyl acetate, dichloromethane, acetone, tetrahydrofuran, and N,N-dimethylformamide. The temperature of the heating and stirring reaction is 75-85° C., and the time of the heating and stirring reaction is 2-4 hours.
6. The preparation method according to claim 1, characterized in that: The stirring reaction time in step S5 is 7-10 hours.
7. The preparation method according to claim 1, characterized in that: The specific steps include: S1. Add 10 parts by weight of polytetrafluoroethylene powder to Augeo SL-191 solvent, irradiate at a temperature of 100-150°C, irradiate at a total dose of 12-15 kGy, add 2-3 parts by weight of glycidyl methacrylate, 0.01-0.02 parts by weight of ammonium ferrous sulfate and 0.02-0.05 g of concentrated sulfuric acid, introduce nitrogen, heat to 60-70°C, stir to react for 3-5 hours, extract with acetone for 24 hours after the reaction is completed, and dry to obtain modified Teflon powder; S2. adding 10 parts by weight of graphene oxide to water, adding 3-4 parts by weight of dopamine hydrochloride and 0.5-1 parts by weight of a catalyst, heating to 45-55° C., stirring for 1-3 hours, filtering, washing, and drying to obtain modified graphene oxide; The catalyst is a Tris-HCl solution with a pH of 9-10; S3. The modified graphene oxide is reduced by hydrazine hydrate vapor for 7-10h to obtain modified graphene; S4. 3-4 parts by weight of phosphorus oxychloride and 10 parts by weight of modified graphene are added to a solvent, heated to 75-85° C., stirred for reaction for 2-4 hours, centrifuged, washed, and dried to obtain a composite; S5. Add 10 parts by weight of modified Teflon powder and 3-5 parts by weight of the composite into 75-85 parts by weight of Teflon primer, and stir to react for 7-10 hours to obtain an anti-corrosion Teflon coating.
8. An anti-corrosion Teflon coating, characterized in that: The anti-corrosion Teflon coating is prepared by the preparation method described in any one of claims 1-7.
9. Use of the anticorrosive Teflon coating according to claim 8 in preparing kitchenware coatings.
Citation Information
Patent Citations
Water-based ultra-fast-drying anticorrosive paint for petroleum steel pipe
CN113913113A
Wear-resistant super-hydrophobic polycarbonate substrate and preparation method thereof
CN115895009A
Modified graphene oxide / polyaniline waterborne epoxy resin anticorrosive paint and preparation method thereof
CN116355500A
Polyurea waterproof composition and preparation method thereof
CN116640499A
High-thermal-conductivity epoxy resin composition based on copper-clad plate and preparation method of high-thermal-conductivity epoxy resin composition
CN118725518A
Cited By
Polytetrafluoroethylene insulated cable and preparation process thereof
CN119626666A
A polytetrafluoroethylene insulated cable and its preparation process
CN119626666B
Composite modified Teflon coating as well as preparation method and application thereof
CN120905967A
Water-based Teflon coating and preparation method thereof
CN120944418A
Aqueous teflon coating and method of making same
CN120944418B